Estimation of the capacitor voltages in flying capacitor multi‐level converters. Issue 3 (20th January 2021) - Escalante, Miguel F.; Erdmann, Alex P.
Abstract: Flying capacitor multi‐level converters use charged capacitors as a critical element. For proper operation, the capacitor voltages must be known and regulated. Direct measurement is straightforward, but when the number of required measurements is high, this is a complicated approach. This paper introduces an estimation method for n capacitor voltages. The scheme is based on a system of ( n + 1 ) equations, which is defined in a way that it incorporates information of the actual capacitor voltages and open‐loop estimates of the capacitor voltages. The solution of the system gives the best estimates of the capacitor voltages in the sense of least square errors. The method requires only output voltage and output current sensors and its computational burden is low, saving cost and design efforts, and simplifying the hardware system. The performance of the proposed scheme is evaluated experimentally in a 9‐level flying capacitor chopper, where the estimates are used by the voltage balancing strategy and by the output current controller.